The Influence of Business Ethics in Entrepreneurship in the Era of Covid-19 Pandemic - Dzaki Maulana Akbar; Morse Kathryn; Ling Barra (Yayasan Adra Karima Hubbi, 2023)
Entrepreneurs in the current era are facing the impact of the Covid-19 pandemic which has caused a decline in sales, raw materials and capital difficulties. This research aims to analyze business actors in understanding the values and rules of business ethics and confirm conformity with the principles of business ethics as well as the application of business ethics during the covid-19 pandemic. This research uses qualitative methods as well as interviews by telephone and meeting directly with business people but still applying health protocols, the respondents in this study were 8 people as entrepreneurs. This research uses qualitative descriptive data analysis. The application of business ethics and business strategies is carried out to realize the sustainability of a business during the ongoing global pandemic and also when the pandemic is over in order to strengthen business management. The results of this study can be used in providing debriefing to every company leader when considering making strategic decisions related to complex morals.